The Epistemology of Prophetic Thinking: Its Relevance to the Aims of Islamic Education - Asman Asman; Musa Asy'arie; Mahasri Shobahiya (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2026)
The contemporary Islamic education system is predominantly implemented through a dogmatic approach, with a primary emphasis on cognitive development and character or moral formation. This study aims to examine the concept of prophetic epistemology and its relevance to the objectives of Islamic education. The main focus of this research is to understand how the prophetic dimension can serve as an epistemological foundation for the construction of Islamic educational knowledge. This study employs a descriptive qualitative approach through a literature review. The primary data sources consist of works by contemporary Islamic thinkers such as Kuntowijoyo, Al-Attas, Al-Faruqi, and Musa Asy’arie. Secondary data are drawn from various relevant journals, books, articles, and other scholarly sources. The data analysis method used in this research is content analysis. The findings indicate that prophetic epistemology is capable of reorienting Islamic education from a mere process of knowledge transmission toward the formation of intelligence that is able to interpret ethical and spiritual realities. At least two significant findings emerge from this study: first, prophetic thinking serves as the epistemological foundation of Islamic education; second, prophetic thinking functions as a conceptual framework within Islamic educational practice. These two aspects can be integrated as the basis for educational objectives that not only enhance intellectual capacity but also cultivate character formation and social responsibility among learners. The implications of this study underscore the necessity of an epistemological reorientation in Islamic education in order to remain relevant to the challenges of modernity without losing its transcendent values. Prophetic epistemology offers a robust philosophical framework for realizing an integrative, humanistic, and revelation-based Islamic education.